Biophysical characterization of small molecule antiviral-loaded nanolipogels for HIV-1 chemoprophylaxis and topical mucosal application. (May 2016) - Ramanathan, R.; Jiang, Y.; Read, B.; Golan-Paz, S.; Woodrow, K.A.
Graphical abstract: Abstract: Nanocarriers are versatile vehicles for drug delivery, and emerging as platforms to formulate and deliver multiple classes of antiretroviral (ARV) drugs in a single system. Here we describe the fabrication of hydrogel-core and lipid-shell nanoparticles (nanolipogels) for the controlled loading and topical, vaginal delivery of maraviroc (MVC) and tenofovir disoproxil fumarate (TDF), two ARV drugs with different mechanisms of action that are used in the treatment of HIV. The nanolipogel platform was used to successfully formulate MVC and TDF, which produced ARV drug-loaded nanolipogels that were characterized for their physical properties and antiviral activity against HIV-1 BaL in cell culture. We also show that administration of these drug carriers topically to the vaginal mucosa in a murine model leads to antiviral activity against HIV-1 BaL in cervicovaginal lavages. Our results suggest that nanolipogel carriers are promising for the encapsulation and delivery of hydrophilic small molecule ARV drugs, and may expand the nanocarrier systems being investigated for HIV prevention or treatment. Statement of Significance: Topical, mucosal intervention of HIV is a leading strategy in the efforts to curb the spread of viral infection. A significant research thrust in the field has been to characterize different dosage forms for formulation of physicochemically diverse antiretroviral drugs. Nanocarriers have been used to formulate and deliver small molecule and protein drugs for a range of applications, including ARV drugs for HIV treatment. The broad significance of our work includes evaluation of lipid-shell, hydrogel-core nanoparticles for formulation and topical, vaginal delivery of two water-soluble antiretroviral drugs. We have characterized these nanocarriers for their physical properties and their biological activity against HIV-1 infection in vitro, and demonstrated the ability to deliver drug-loaded nanocarriers in vivo .